Hitler's last days : the death of the Nazi regime and the world's most notorious dictator - O'Reilly, Bill (Henry Holt and Co., 2015)
"By early 1945, the destruction of the German Nazi State seems certain. The Allied forces, led by American generals George S. Patton and Dwight D. Eisenhower, are gaining control of Europe, leaving German leaders scrambling. Facing defeat, Adolf Hitler flees to a secret bunker with his new wife, Eva Braun, and his beloved dog, Blondi. It is there that all three would meet their end, thus ending the Third Reich and one of the darkest chapters of history"--Provided by publisher.